Combined inertial and pleated filter for efficient PM1.0 separation and sampling - Kwon, Min-Seon; Yoo, Myungsoo; Park, Jinsoo; Lee, Myong-Hwa (Separation and purification technology, 2025)
[Display omitted] •Filter-based PM1.0 sampler was proposed.•I/P sampler collects particles larger than 1 μm and PM1.0 at the same time.•Good correlation between I/P sampler and conventional sampling devices.•Humidity is a critical parameter to determine PM1.0 mass concentration. A reliable measuring method of particulate matter less than 1 µm (PM1.0) is essential to clarify the correlation between the PM1.0 mass concentration and the impact of human health, and to establish effective PM1.0 control strategies. In this study, a new PM1.0 sampler, the inertial filter/pleated filter sampler (I/P sampler), was designed to collect particles larger than 1 μm in the inertial filter and PM1.0 in the pleated filter during sampling. The inertial filter with small filtration area successfully separated particles larger than 1 μm by reducing diffusion and increasing inertia, while the pleated filter with large filtration area efficiently collected PM1.0 by lowering the filtration velocity to promote diffusional collection. The I/P sampler was used to measure PM1.0 mass concentration through field tests, with results compared with those of conventional sampling devices for PM1.0 (cyclone sampler, cascade impactor, beta attenuation monitor [BAM], and EPA-approved federal reference method [E-FRM] sampler). Field measurements indicated a good correlation between the I/P sampler and conventional samplers, with regression slopes ranging from 0.90 to 1.07 in summer and 1.10 to 1.37 in winter. In addition, the measured mass concentrations decreased in the order of I/P sampler, cyclone sampler, E-FRM sampler, BAM, and cascade impactor.